The Influence of Price and Service Quality on Purchasing Decisions of Bhinneka PGRI University Economics Study Program Students on the Shopee E-Commerce Platform - Usbaniyah, Fitria; Hastuti, Maria Agatha Sri Widyanti (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
This research aims to determine the influence of price on purchasing decisions, determine the influence of service quality on purchasing decisions, and to determine the influence of price and service quality on purchasing decisions of students of the Bhinneka PGRI University Economic Education Study Program on the Shopee e-commerce platform. Based on the research method, this research is a type of descriptive quantitative research with a non-experimental approach. This research consists of 2 (two) independent variables, namely price (X1) and service quality (X2), and 1 (one) dependent variable, namely purchasing decisions (Y). The population in this study was all students of the VII semester Economic Education Study Program, totaling 89 students, while the total sample in this study was 89 students. Samples were taken using the Purposive Random Sampling sampling technique. The object of this research is purchasing decisions among students of the Economic Education Study Program at Bhinneka PGRI University. The data collection method in this research is in the form of a questionnaire which is used to search for price data (X1), service quality (X2), and purchasing decisions (Y). The data analysis technique used is multiple linear regression analysis.